Can environmentally themed music increase consumers' willingness to pay for low-carbon food? A discrete choice experiment method - Wang, Zuoyi; Li, Kai (Frontiers in Sustainable Food Systems, 2023)
Transitioning to low-carbon food consumption is indispensable for adapting to and mitigating climate change. Nevertheless, altering dietary habits presents a host of formidable challenges. Using Michael Jackson's renowned environmental-themed song, "Earth Song", as a case study, this article employed a choice experiment to examine its potential impact on facilitating the transition to low-carbon food consumption. The findings revealed the following key insights: Firstly, Consumers show concerns about food safety, nutrients, and unnaturalness of the cell-cultured beef, demonstrating the existence of food neophobia or distrust of novelties in cell-cultured beef. Secondly, while the inclusion of environmentally themed music did not completely eliminate consumers' food neophobia, it undeniably played a pivotal role in significantly improving their willingness to pay (WTP) for cell-cultured meat. This effect was achieved by effectively conveying environmental information, stimulating guilt and responsibility, and igniting consumers' enthusiasm for environmental protection. Thirdly, the introduction of "Earth Song" caused a crowding-out effect on eco-friendly packaging and carbon labeling, and reshaped trust in distribution channels. These impacts are all related to the high price of low-carbon food. All these conclusions underscore the substantial role that environmental-themed music can play in promoting low-carbon foods and valuable insights for policymakers and low-carbon food producers.